Low-field thermal mixing in [1-13C] pyruvic acid for brute-force hyperpolarization - Peat, David T.; Hirsch, Matthew L.; Gadian, David G.; Horsewill, Anthony J.; Owers-Bradley, John R.; Kempf, James G. (Royal Society of Chemistry, 2016)
We detail the process of low-field thermal mixing (LFTM) between 1H and 13C nuclei in neat [1-13C] pyruvic acid at cryogenic temperatures (4–15 K). Using fast-field-cycling NMR, 1H nuclei in the molecule were polarized at modest high field (2 T) and then equilibrated with 13C nuclei by fast cycling (∼300–400 ms) to a low field (0–300 G) that activates thermal mixing. The 13C NMR spectrum was recorded after fast cycling back to 2 T. The 13C signal derives from 1H polarization via LFTM, in which the polarized (‘cold’) proton bath contacts the unpolarised (‘hot’) 13C bath at a field so low that Zeeman and dipolar interactions are similar-sized and fluctuations in the latter drive 1H–13C equilibration. By varying mixing time (tmix) and field (Bmix), we determined field-dependent rates of polarization transfer (1/τ) and decay (1/T1m) during mixing. This defines conditions for effective mixing, as utilized in ‘brute-force’ hyperpolarization of low-γ nuclei like 13C using Boltzmann polarization from nearby protons. For neat pyruvic acid, near-optimum mixing occurs for tmix ∼ 100–300 ms and Bmix ∼ 30–60 G. Three forms of frozen neat pyruvic acid were tested: two glassy samples, (one well-deoxygenated, the other O2-exposed) and one sample pre-treated by annealing (also well-deoxygenated). Both annealing and the presence of O2 are known to dramatically alter high-field longitudinal relaxation (T1) of 1H and 13C (up to 102–103-fold effects). Here, we found smaller, but still critical factors of ∼(2–5)× on both τ and T1m. Annealed, well-deoxygenated samples exhibit the longest time constants, e.g., τ ∼ 30–70 ms and T1m ∼ 1–20 s, each growing vs. Bmix. Mixing ‘turns off’ for Bmix > ∼100 G. That T1m ≫ τ is consistent with earlier success with polarization transfer from 1H to 13C by LFTM.